Antimicrobial resistance profiles of Staphylococcus spp. and Escherichia coli isolated from dogs and cats in Seoul, South Korea during 2021–2023 - Seo, Ye-Ram; Choi, Sue-young; Kim, Sori; Kang, Kyoung-suk; Ro, Chang-seek; Hyeon, Ji-Yeon (Frontiers in Veterinary Science, 2025)
We investigated the antimicrobial resistance (AMR) rates and profiles of Staphylococcus spp. and Escherichia coli (E.coli) isolated from dogs and cats in Seoul, South Korea during 2021–2023. We analyzed AMR profiles of Staphylococcus spp. and E. coli isolated from 2,180 samples (1,859 canine and 321 feline) collected from 36 veterinary clinics in Seoul, South Korea, as part of the Korean Veterinary Antimicrobial Resistance Monitoring System (2021–2023). A total of 484 Staphylococcus spp. isolates and 158 E. coli isolates were identified and used for AMR test. Staphylococcus spp. isolates exhibited the highest resistance to penicillin in both dogs (85%) and cats (29.81%). Multidrug-resistant (MDR) Staphylococcus spp. was more prevalent in dogs (65%) than in cats (14.42%), with three S. pseudintermedius isolates from dogs and a S. pseudintermedius isolate from a cat showing resistance to eight antibiotic classes. Methicillin-resistant S. pseudintermedius (MRSP) constituted 105 out of 284 S. pseudintermedius isolates (36.97%) in dogs and seven strains out of 14 (50%) in cats. E. coli isolates demonstrated the highest resistance to cefalexin in both dogs (61.72%) and cats (56.67%). The prevalence of MDR E. coli was higher in dogs (37.5%) than in cats (26.67%). This study highlights the concerning prevalence of AMR in commensal or potentially opportunistic pathogens from companion animals, particularly in dogs. It is crucial to promote the prudent use of antimicrobials in companion animals and ensure the ongoing monitoring of trends in antimicrobial-resistant bacteria to mitigate the selection and spread of antibiotic-resistant bacteria between humans and companion animals.